Research on the evaluation indicator system of teaching quality for graduate students in Health Management - Gao, Hongda; Xu, Tingting; Jiang, Nan; Chen, He (Acta Bioethica, 2025)
This study aimed to develop a comprehensive evaluation indicator system for assessing the teaching quality (TQ) of graduate students majoring in Health Management. The evaluation indicator system was built using the Delphi Method with 20 senior experts who have extensive experience in health management education and research. The final evaluation system was applied in a case study at Guangxi Medical University. The weight of Teaching Staff (0.381) and Teaching Target (0.381) is higher than that of the Teaching Process (0.237). In the Teaching Staff dimension, experts emphasize that Professional Qualities (0.057) play a key role in TQ, especially Teaching Reflection (0.255) and Political Literacy (0.255). In the Teaching Target dimension, Student Research Output (0.072) and Assessment Criteria (0.065) are the core factors. In the Teaching Process dimension, the weight of Teaching Methods (0.565) is higher than that of Teaching Content (0.435). For the Teaching Staff, experts and students agree that the weight of Professional Expertise is the lowest. In summary, the Professional Qualities in Teaching Staff dimension, especially Teaching Reflection and Political Literacy, are the key factors affecting TQ. Student Research Output and Assessment Criteria are the core factors in the evaluation of Teaching Target.